2015
DOI: 10.5713/ajas.15.0165
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Mycotoxins from Contaminated Corn with or without Yeast Cell Wall Adsorbent on Broiler Chickens

Abstract: This study investigated the effects of feeds naturally contaminated with mycotoxins on growth performance, serum biochemical parameters, carcass traits, and splenic heat shock protein 70 (Hsp70) mRNA expression levels in broiler chickens. The efficacy of yeast cell wall (YCW) adsorbent in preventing mycotoxicosis was also evaluated. Three hundred 1-d-old Arbor Acres broiler chicks were randomly allotted to 3 treatments in completely randomized design for 42 d. Each treatment group had 5 replicate pens with 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
7
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
4
7
0
2
Order By: Relevance
“…The results of the present study are in agreement with that from Ji et al (2016) and Shang et al (2016), who revealed that mycotoxin decreased lipid blood parameters. Decreased cholesterol levels may be attributed to the hepatotoxic effects of AFB and OTA or their synergetic effect that is characterised by impairment of transport and lipid metabolism of liver (Shang et al 2016). The HDL can remove cholesterol from the blood vessels and carries it back to the liver, where it can be processed and sent out of the body.…”
Section: Effect Of Mycotoxinssupporting
confidence: 93%
See 1 more Smart Citation
“…The results of the present study are in agreement with that from Ji et al (2016) and Shang et al (2016), who revealed that mycotoxin decreased lipid blood parameters. Decreased cholesterol levels may be attributed to the hepatotoxic effects of AFB and OTA or their synergetic effect that is characterised by impairment of transport and lipid metabolism of liver (Shang et al 2016). The HDL can remove cholesterol from the blood vessels and carries it back to the liver, where it can be processed and sent out of the body.…”
Section: Effect Of Mycotoxinssupporting
confidence: 93%
“…Furthermore, the decreased IgA production observed in this study may be related to the reduction of T lymphocytes as well as cytokines induced by AFB and OTA. It is well demonstrated that broilers fed with the dosage of 0.3 mg/kg AFB diet showed a decline population of T cells in the peripheral blood and decreases of mature T cell number and some cytokine (IL-2 and IL-6) mRNA expression in the ileum (Shang et al 2016).…”
Section: Effect Of Mycotoxinsmentioning
confidence: 99%
“…Mycotoxins can be harmful to hosts. Mycotoxincontaminated feed may lead to consequences such as poor growth performance and meat quality, low nutrient digestibility, and increased disease incidence due to immunosuppression, all of which may result in economic losses (Swamy et al, 2002;Shang et al, 2016). Aflatoxin (AF) is a mycotoxin that particularly affects poultry and often occurs in naturally contaminated feeds (Aravind et al, 2003;Murugesan et al, 2015).…”
Section: The Effect Of Hydrated Sodium Calcium Aluminosilicate On Fatmentioning
confidence: 99%
“…๊ณฐํŒก์ด ๋…์†Œ์— ์˜ค์—ผ๋œ ์‚ฌ๋ฃŒ์˜ ๊ฒฝ์šฐ, ํ•œ๊ฐ€์ง€ ์ด์ƒ์˜ ๊ณฐํŒก ์ด๋ฅผ ํฌํ•จํ•˜๋ฉฐ, ํ•œ ์ข…์˜ ๊ณฐํŒก์ด๊ฐ€ ํ•˜๋‚˜ ๋˜๋Š” ์—ฌ๋Ÿฌ ์ข…๋ฅ˜์˜ ๋… ์†Œ๋ฅผ ์ƒ์‚ฐํ•˜๊ณ , ๊ฐ๊ฐ์˜ ๊ณฐํŒก์ด ๋…์†Œ๋Š” ๋‹ค๋ฅธ ๊ณฐํŒก์ด์— ์˜ํ•ด์„œ ์ƒ์‚ฐ๋  ์ˆ˜ ์žˆ๋‹ค (Hussein and Brasel, 2001;Lee et al, 2002). ์—ฌ๋Ÿฌ ์ข…์˜ ๊ณฐํŒก์ด ๋…์†Œ๊ฐ€ ์˜ค์—ผ๋œ ์‚ฌ๋ฃŒ์˜ ๊ฒฝ์šฐ, ์„ญ์ทจ ์‹œ ์ƒ์Šน ์ž‘์šฉ์œผ๋กœ ์ถ”๊ฐ€์ ์ธ ๋…์„ฑ์„ ์œ ๋ฐœํ•  ์ˆ˜ ์žˆ๋‹ค (Shang et al, 2015).…”
Section: ์„œ ๋ก unclassified